Beyond cop cities: dismantling state and corporate-funded armies and prisons - James, Joy (Pluto Press, 2024)
"Since 1997, the US Department of Defense has transferred more than $7.2bn in military equipment to law enforcement agencies. Furthermore, the DOD is legally required to make various items of equipment available to local police and school police departments, from flashlights and sandbags, to grenade launchers and armored vehicles. This militarisation has, unsurprisingly, been shown to unjustly impact on Black communities and is associated with increased killings by police. No wonder there have been calls to 'defund the police' echoing across the streets of America. In Beyond Cop Cities, Joy James and fellow contributors take these calls one step further, highlighting the Stop Cop City movement - one of the most vibrant in the US today. Linking anti-policing and racial justice movement with radical ecological 'forest defender' activism, the Stop Cop City campaign is a grass roots movement which aims to push back on police militarisation by blocking the construction of Atlanta's Police Public Safety Training Center. Sharp and concise, including the voices of key figures in the movement along with the mother of murdered activist 'Tortuguita' (shot and killed by Georgia police while protesting), this collection of vital and politically sophisticated writings capture a moment in time, demanding a safer, less brutal, future." --